Association Between Type 2 Diabetes Mellitus and the Presence of Myocardial Ischemia among Filipino Patients with Stress Myocardial Perfusion Scintigraphy - Cañizares, H G; Ogbac, M D (KnE Social Sciences, 2018)
Background: Type 2 DM patients usually had poor prognosis for CAD. MPS with SPECT has been extensively used in CAD detection and it’s application among type 2 DM population is still under study with promising result. In the Philippines, there are no current available data regarding this matter. Methodology: This was a cross sectional analytical study of randomly selected Filipino patients without previous cardiac events in whom MPS using Thallium-201 were performed over a 24-month period. Association of myocardial ischemia was compared using logistic regression analysis based on total summed stress score (SSS) values. Results: Total of 208 patients (104 type 2 DM and 104 non-type 2 DM) who underwent stress or pharmacologic MPS using Thallium-201 were included in the study. Majority of the subjects were male. Abnormal 2D echo result and lower EF were significantly present among type 2 DM group (p = 0.044, 0.0005). Hypertension was more prominent among the list of co-morbidities and has significant relationship with type 2 DM group (p = 0.025). The distribution of myocardial ischemia among type 2 DM group with insignificant, mildly abnormal, and moderate to severely abnormal; were 60.6%, 12.5%, and 26.9%, respectively. The presence of having significant CAD (SSS>3) was associated with the type 2 DM group with odds ratio of 2.57 (95% CI: 1.38-4.78, p = 0.003). Conclusion: The current study has shown that Filipino type 2 DM patients without previous cardiac events are likely to have significant and more severe scintigraphic evidence of CAD than their non-type 2 DM counterpart. Keywords: coronary artery disease, Filipino type 2 diabetic patients, myocardial perfusion scintigraphy, myocardial ischemia, summed stress score